IBM DS8900F Architecture and Implementation Updated for Release 9.2 - Dufrasne, Bertrand; Brunson, Sherri; Cook, Jeff; Martinez, Lisa; Riggins, Connie; Stenson, Mike (IBM Redbooks, 2021)
This IBM® RedpaperRedbooks® publication describes the concepts, architecture, and implementation of the IBM DS8900F family. The WhitepaperRedpaperbook provides reference information to assist readers who need to plan for, install, and configure the DS8900F systems. This edition applies to DS8900F systems with IBM DS8000® Licensed Machine Code (LMC) 7.9.20 (bundle version 89.20.xx.x), referred to as Release 9.2. The DS8900F is an all-flash system exclusively, and it offers three classes: DS8980F: Analytic Class: The DS8980F Analytic Class offers best performance for organizations that want to expand their workload possibilities to artificial intelligence (AI), Business Intelligence (BI), and machine learning (ML). IBM DS8950F: Agility Class all-flash: The Agility Class consolidates all your mission-critical workloads for IBM Z®, IBM LinuxONE, IBM Power Systems, and distributed environments under a single all-flash storage solution. IBM DS8910F: Flexibility Class all-flash: The Flexibility Class reduces complexity while addressing various workloads at the lowest DS8900F family entry cost. . TThe DS8900F architecture relies on powerful IBM POWER9"!processor-based servers that manage the cache to streamline disk input/output (I/O), which maximizes performance and throughput. These capabilities are further enhanced by High-Performance Flash Enclosures (HPFE) Gen2. Like its predecessors, the DS8900F supports advanced disaster recovery (DR) solutions, business continuity solutions, and thin provisioning. The IBM DS8910F Rack-Mounted model 993 is described in IBM DS8910F Model 993 Rack-Mounted Storage System Release 9.1, REDP-5566
Online resource; Title from title page (viewed September 16, 2021)